Atomic Layer Deposition of High‐Capacity Anodes for Next‐Generation Lithium‐Ion Batteries and Beyond. Issue 3 (25th October 2020) - Cao, Yanqiang; Meng, Xiangbo; Li, Aidong
Abstract : Electrification has great impacts on our modern society. To electrify future transportation, state‐of‐the‐art lithium‐ion batteries (LIBs) are still not sufficient in multiple aspects including cost, energy density, lifespan, and safety. To this end, next‐generation high‐energy LIBs and beyond are highly regarded. In this regard, high‐capacity anodes are undergoing intensive investigation, such as silicon, SnO2, and lithium metal. However, such anode materials are commonly experiencing large volume changes and related issues, which are reflected on mechanical degradation, capacity fading, low efficiency, and unsatisfactory lifetime. To address these challenges, many technical strategies have been investigated. In the past decade, atomic layer deposition (ALD) has emerged as a new promising technique enabling atomic‐scale surface modification and nanoscale design of high‐capacity anodes for high performance. In this review, recent ALD studies on developing high‐capacity anodes for LIBs and beyond are thoroughly summarized. In addition, ALD strategies and their effectiveness in pursing high‐energy LIBs and beyond are discussed. Particularly, we highlighted the latest advances of ALD for addressing the notorious issues associated with Li metal anodes. It is expected that this work will promote the applications of ALD in new battery systems. Abstract : High‐capacity anodes are essential for high‐energy density lithium‐ion batteries (LIBs) and beyond. Unfortunately, these anodes commonly suffer from mechanical degradation and resultant capacity fading, which must be addressed before commercialization. Atomic layer deposition (ALD) shows great prospects in solving above issues. This thorough review summarizes ALD studies and strategies for developing high‐capacity anodes for LIBs and beyond.